Host population density and presence of predators as key factors influencing the number of gregarious parasitoid Anaphes flavipes offspring - Samková, Alena; Hadrava, Jiří; Skuhrovec, Jiří; Janšta, Petr (Scientific reports, 2019)
The number of parasitoids developed per host is one of the major factors that influences future adult body size and reproductive success. Here, we examined four external factors (host species, heritability, host population density, and presence of predators) that can affect the number of the gregarious parasitoid Anaphes flavipes (Förster, 1841) (Hymenoptera: Mymaridae) wasps developing in one host. The effect of host population density on the number of parasitoid offspring developed per host was confirmed, and for the first time, we also showed that the number of offspring per host is influenced by the presence of predators. Low host density and presence of predators increases the number of wasps developed in one host egg. However, a higher number of A. flavipes in one host reduces A. flavipes body size and hence its future individual fertility and fitness. Our results highlighted the importance of some external factors that distinctly affect the number of wasp offspring. Therefore, in this context, we suggest that in comparison to solitary parasitoids, the gregarious parasitoid A. flavipes can better respond to various external factors and can more flexibly change its population density.
Keywords: Host Specificity; Wasps; brouci; Body Size; hostitelská specificita; hustota populace; sršňovití; Host-Parasite Interactions; Reproduction; fertilita; Animals; rozmnožování; Population Density; velikost těla; interakce hostitele a parazita; zvířata; Fertility; Coleoptera